Exercise sustains motor function in Parkinson's disease: Evidence from 109 randomized controlled trials on over 4,600 patients - Zhang, Meiqi; Li, Fang; Wang, Dongyu; Ba, Xiaohong; Liu, Zhan (Frontiers in Aging Neuroscience, 2023)
Physical exercise has been widely identified as a supplementary therapy for Parkinson’s disease (PD). Evaluating changes in motor function over long-term periods of exercise and comparative efficacy of various exercise types will enable a better understanding of the effects of exercise on PD. A total of 109 studies that covered 14 types of exercise were included in the analyses, enrolling 4631 PD patients. Meta-regression revealed that chronic exercise delays the progression of PD motor symptoms, mobility, and balance decline; Nevertheless, for the non-exercise PD groups, motor function progressively declined. Results from network meta-analyses suggest that dancing is the optimal exercise for general motor symptoms, Nordic walking is the most efficient exercise to mobility and balance performance, and Qigong may have specific benefit in improving hand function. The study confirmed the effects that chronic exercise preserves the progression of motor decline in PD while proposing dancing, yoga, multimodal training, Nordic walking, aquatic training, exercise gaming, and Qigong as superior PD exercises. (PROSPERO registration: CRD42021276264)